Students’ worksheets on work and energy using kokami media: An effort to increase the student’s cognitive achievement - Mastuang, Mastuang; Sa'adah, Alfis; Hartini, Sri; Wati, Mustika; Mahtari, Saiyidah; Misbah, Misbah; Sulaeman, Nurul F (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2020)
This study aims to describe the feasibility of student worksheets on natural science with Kokami (Kotak Kartu misterius/ mysterious card box) media to increase the students’ learning outcome. The themes of the developed product are work and energy for junior high school level students. The specific objectives of this study were to describe the validity, practicality, and effectiveness of natural science students' worksheets with Kokami media. The type of this research is research and development with the ADDIE development model. The test subjects were 36 students from one of the public junior high school in Barito Kuala regency. The instruments of this research were validation sheets, questionnaires, and learning outcomes tests. The results showed that: 1) the validity of students’ worksheets of natural science with the Kokami media was included in the highly valid category, (2) the practicality of students’ worksheets of natural science with the Kokami media was in the very good category, and (3) the effectiveness of students’ worksheets of natural science with Kokami media was in the high category. It can be concluded that the natural science students' worksheets with Kokami media were feasible to be used at the junior high school level. Kokami media can be an effective and attractive alternative learning media in learning physics